Psychomotor activities in the context of kinanthropology: Review - Běla Hátlová; Iva Wedlichová; Milena Adámková Ségard (Palacký University Olomouc, 2015)
BACKGROUND: Any scholar developing a therapeutic method shall be concerned with its historical and theoretical groundings, scientifically verified facts, and information from professional publications. As a result of that, one is qualifi ed to discuss relevancy of the method. OBJECTIVES: The aim of this study is to highlight the ideas that the current psychomotoricity draws. METHODS: We assume that psychomotor activity is based on natural cognitive and social movement behavior. In its essence, the inherited principles that develop throughout life. Development is strengthened primarily by personal experiences with positive and negative feedback of social relations. The foundations of psychomotr activity developed upon scientific knowledge stem from the needs of psychosomatic rehabilitation. The term gradually came to be used for movement therapies and movement education. This study mentions the scientific orientations and the authors who most influenced the development of psychomotor skills used for personal development. CONCLUSION: Psychomotor activities are developed from two basic areas of operation. Psychomotor development as a pedagogical direction linking the physical and mental is used in the teaching process with an eff ort by moving positively with an influence from the human psyche. By monitoring the simple actions there is stimulated the physical and psychical development. Psychomotor development and sports therapy inherently encourages the patient to actively participate in therapy. Physical activity is one of supporting policies which affect the psychical „negative“ symptoms and may enhance the patient’s resistance to daily stress.